Earnings Management As A Pathway Between Rpt, Capital Intensity, And Tax Aggressiveness: Audit Quality Perspective - Napisah Napisah; Yuliana Sari (JURNAL ECONOMINA, 2026)
This study examines the effect of Related Party Transactions (RPT) and Capital Intensity (CI) on Tax Aggressiveness, with Earnings Management serving as an intervening variable and Audit Quality as a moderating variable. The study employs a quantitative approach using industrial sector companies listed on the Indonesia Stock Exchange during the 2019–2023 period. The final sample consists of 12 companies, resulting in 60 firm-year observations. Panel data regression analysis is employed to test the proposed hypotheses. The results indicate that Related Party Transactions do not affect Earnings Management but have a positive effect on Tax Aggressiveness, and this relationship is not mediated by Earnings Management. In contrast, Capital Intensity positively affects Earnings Management but does not significantly affect Tax Aggressiveness, although its effect on Tax Aggressiveness is mediated by Earnings Management. Furthermore, Earnings Management has a significant negative effect on Tax Aggressiveness, while Audit Quality does not moderate the relationship between Earnings Management and Tax Aggressiveness.